2020
DOI: 10.1186/s12883-020-01712-5
|View full text |Cite
|
Sign up to set email alerts
|

Multiple reversible encephalitic attacks: a rare manifestation of neuronal intranuclear inclusion disease

Abstract: Background: Neuronal intranuclear inclusion disease (NIID) is a rare neurodegenerative condition characterized by the loss of neurons and the presence of eosinophilic nuclear inclusions in the central and peripheral nervous system, skin and visceral organs. In this paper, we present a case of NIID with recurrent encephalitic attacks that remained stable and nonprogressive for seven years; no such case has previously been reported. Case presentation: A 63-year-old female was hospitalized due to light-headedness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…Among our patients, two patients even consulted the doctor with headache as the earliest and main clinical symptom. Hemiplegic migraine was once reported as rare clinical manifestations in 2019, no other types of headache were reported yet (18)(19)(20). However, the previous literature rarely included headache among the common symptoms of NIID.…”
Section: Discussionmentioning
confidence: 99%
“…Among our patients, two patients even consulted the doctor with headache as the earliest and main clinical symptom. Hemiplegic migraine was once reported as rare clinical manifestations in 2019, no other types of headache were reported yet (18)(19)(20). However, the previous literature rarely included headache among the common symptoms of NIID.…”
Section: Discussionmentioning
confidence: 99%
“…1 MRI scans on the 5th day after admission: a The T2/FLAIR sequence: the arrow refers to abnormal signals in the white matter region of the brain, b DWI imaging: the arrow refers to high intensity areas in the cerebral white matter and grey matter-white matter junction; the MRI was conducted on the 20th day after admission: c The T2/FLAIR sequence: the arrow refers to abnormal signals in the white matter region of the brain, d DWI imaging: the arrow refers to high intensity areas in the cerebral white matter and grey matter-white matter junction. Cranial computed tomography scans showed a low-density lesion in the white matter, area-brain atrophy, and leucoencephalopathy: e in 2012, f in 2018, and g this hospitalization weakness, and Li et al reported a patient with multiple reversible encephalitic attacks, with light-headed episodes, central facial paralysis, unstable gait, aphasia, nausea, vomiting and loss of consciousness [16,17]. However, no cases have yet been reported with strokelike onset symptoms and encephalitic attacks.…”
Section: Discussionmentioning
confidence: 99%
“…However, NIID symptoms are highly heterogenous, and overlap between subgroups is observed frequently, with variable muscle weakness associated with various dysfunctions of the central and peripheral nervous systems, which can include progressive dementia and cognitive impairment, parkinsonism, cerebellar ataxia, sensory disturbance, autonomic dysfunction, and/or peripheral neuropathy ( Takahashi-Fujigasaki, 2003 ; Sone et al., 2016 ; Takahashi-Fujigasaki et al., 2016 ). Moreover, individuals with NIID with atypical presentation, such as essential tremors, multiple-systems atrophy, and amyotrophic lateral sclerosis, and various acute symptoms, including stroke-like episodes, epileptic seizures, and/or encephalitic episodes, have also been reported ( Sone et al., 2016 ; Fang et al., 2020 ; Li et al., 2020 ; Sun et al., 2020 ; Yuan et al., 2020 ). As a consequence of these diverse ages of onset and clinical presentations, NIID diagnosis is most often confirmed by the widespread presence of characteristic eosinophilic intranuclear inclusions in neurons and glial cells in the central and peripheral nervous systems and in various other tissues ( Chen et al., 2020a , Liu et al., 2008 , Sone et al., 2005 , Sone et al., 2011 , Sone et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%